KORELASI NILAI LAJU ENDAP DARAH (LED) DENGAN HIGH SENSITIVITY C-REACTIVE PROTEIN (hs-CRP) PADA PEROKOK AKTIF DI WARUNG KOPI WILAYAH SURABAYA TIMUR - Ramadhany, Rieke Dwi; Woelansari, Evy Diah; Rahayuningsih, Christ Kartika; Aprilyadi, Nadi (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2022)
Background Smoking has become one of the leading causes of death worldwide. The negative impact of smoking usually occurs after a few years when a person starts actively smoking can harm the body's organs and become a major risk factor for diseases with inflammatory components. Systemic inflammatory reactions are characterized by an increase in inflammatory cytokines, blood cell counts and blood viscosity. Examination CRP and ESR are the two most frequently measured laboratory tests in assessing the response of a systemic inflammatory process. This study aims to determine and analyze the correlation between ESR values ​​and hs-CRP in active smokers at coffee shops, East Surabaya. Methods: The type of research used is correlation research with cross sectional. The sample used is 30 active smokers who meet the inclusion criteria. This research was carried out on February 21 – April 11, 2022. The examination of ESR values ​​and hs-CRP levels was carried out at Balai Besar Laboratorium Kesehatan (BBLK) Surabaya. Results: It was found that 30 respondents had been actively smoking >5 years with a percentage of 100%. as many as 8 respondents consumed 1-10 cigarettes/day with a percentage of 27%, 19 respondents consumed 10-20 cigarettes per/with a percentage of 63%, and 3 respondents consumed >20 cigarettes/day with a percentage of 10%. The average value of ESR is 8.37 mm/Hr and The The average value of the of hs-CRP 1.11 mg/L. Conclusion: Based on statistical tests, There is no correlation between the value of ESR and hs-CRP in active smokers in a coffee shop in the East Surabaya area (p value = 0.099) with a sufficient relationship and a positive direction of relationship (r = 0.307).